Spent Hop (Humulus lupulus L.) Extract and Its Flaxseed Polysaccharide-Based Encapsulates Attenuate Inflammatory Bowel Diseases Through the Nuclear Factor-Kappa B, Extracellular Signal-Regulated Kinase, and Protein Kinase B Signalling Pathways - Miłosz Caban; Katarzyna Owczarek; Justyna Rosicka-Kaczmarek; Karolina Miśkiewicz; Joanna Oracz; Wojciech Pawłowski; Karolina Niewinna; Urszula Lewandowska (Cells)
The treatment of inflammatory bowel diseases (IBDs), particularly ulcerative colitis and Crohn’s disease, remains a challenge. As the available therapeutic options have limited efficacy and various side effect, there is a need to identify new inflammatory modulators that can influence IBD. Natural polyphenols and polyphenol-rich extracts have been found to have preventive and therapeutic potential, including various anti-inflammatory effects. In this study, the inhibition of the formation of mediators associated with intestinal inflammation, remodelling, and angiogenesis by the spent hop extract (SHE), a polyphenol-rich extract from Humulus lupulus L., and its flaxseed polysaccharide-based encapsulates was examined using tumour necrosis factor alpha (TNF-α)-stimulated human small intestinal epithelial (HIEC-6) and large intestinal epithelial (CCD841CoN) cells. Also, we assessed the activity of the tested agents after in the vitro-simulated gastrointestinal digestion process. SHE strongly inhibited the expression of pro-inflammatory cytokines, mainly IL-1β and TNF-α, as well as the expression and activity of type IV collagenases (MMP-2 and MMP-9); these effects resulted from the suppression of NF-κB, ERK and Akt signalling pathways. We also proved the protective effect of encapsulation process against the reduction in the bioaccessibility of SHE, observed under the influence of digestion process. Our results provide initial evidence on the potential utility of SHE and its encapsulates in IBD.